Kemampuan Pemecahan Masalah Siswa pada Materi Bangun Ruang Melalui Collaborative Problem Solving - Lidya Yuni Kartika; Rooselyna Ekawati (Universitas Negeri Surabaya, 2026)
Problem-solving ability is an important skill for students because it is the main indicator of success in learning mathematics, especially in spatial geometry material that requires conceptual understanding and appropriate strategy application. This study is a descriptive qualitative study that aims to describe students' problem-solving abilities in spatial geometry material through Collaborative Problem Solving (CPS) by comparing homogeneous and heterogeneous student groups. This study was conducted on eighth-grade students at SMP Negeri 23 Surabaya in the odd semester of the 2025/2026 academic year. The research subjects consisted of six students who were grouped into two groups, namely one homogeneous group with high mathematical abilities and one heterogeneous group consisting of students with high, medium, and low abilities. Research data were collected through mathematical ability tests, spatial geometry problem-solving ability tests carried out collaboratively, and interviews. The results showed that students' problem-solving abilities were analyzed using Polya indicators collaboratively. Homogeneous groups were able to demonstrate a more systematic and balanced problem-solving process in understanding problems, making plans, implementing plans, and evaluating solutions. The research findings indicate that group composition influences student problem-solving.